Burnout and Hypocortisolism – A Matter of Severity? A Study on ACTH and Cortisol Responses to Acute Psychosocial Stress - Lennartsson, Anna-Karin; Sjörs, Anna; Währborg, Peter; Ljung, Thomas; Jonsdottir, Ingibjörg H. (Frontiers in Psychiatry, 2015)
Background: Common consequences of long-term psychosocial stress are fatigue and burnout. It has been suggested that burnout could be associated with hypocortisolism, thus, inability to produce sufficient amounts of cortisol. This study aimed to investigate whether patients with clinical burnout exhibit aberrant ACTH and cortisol responses under acute psychosocial stress compared with healthy individuals. Methods: Nineteen patients (9 men and 10 women) and 37 healthy subjects (20 men and 17 women), underwent the Trier Social Stress Test. Blood samples and saliva samples were collected before, after and during the stress test for measurements of plasma ACTH, serum cortisol and salivary cortisol. Several statistical analyses were conducted to compare the responses between patients and controls. In addition, in order to investigate the possibility that burnout patients with more severe symptoms would respond differently, sub-groups of patients reporting higher and lower burnout scores were compared. Results: In both patients and healthy controls, we observed elevated levels of ACTH and cortisol after exposure to the stressor. There were no differences in responses of ACTH, serum cortisol or salivary cortisol between patients and controls. Patients reporting higher burnout scores had lower salivary cortisol responses than controls, indicating that patients with more severe burnout symptoms may be suffering from hypocortisolism. In addition patients with more severe burnout symptoms tended to have smaller ACTH responses than the other patients. There was no corresponding difference in serum cortisol however. Conclusion: This study indicates that hypocortisolism is not present in a clinical burnout patient group as a whole but may be present in the patients with more severe burnout symptoms.